Reproducibility of the Geomagnetically Induced Currents at Middle Latitudes During Space Weather Disturbances - Kikuchi, Takashi; Ebihara, Yusuke; Hashimoto, Kumiko. K.; Kitamura, Kentaro; Watari, Shin-Ichi (Frontiers in Astronomy and Space Sciences, 2021)
Watari et al. [SW2009] found that the geomagnetically induced current (GIC) in Hokkaido, Japan (35.7° geomagnetic latitude (GML)) is well correlated with the y-component magnetic field (By) (correlation coefficients > 0.8) and poor correlations with Bx,z and dBx,y,z/dt. The linear correlation with By would help predict the GIC, if we have capabilities of reproducing the magnetosphere-ionosphere currents during space weather disturbances. To validate the linear correlation with By for any periods (T) of disturbances, we made correlation analyses for the geomagnetic sudden commencements and pulsations (T = 1-10m), quasi-periodic DP2 fluctuations (30m), substorm positive bays (60m), geomagnetic storms (1-20h) and quiet-time diurnal variations (8h). The linear correlation is found to be valid for short periods (cc > 0.8 for T < 1 h), but not for long periods (cc < 0.3 for T > 6 h). To reproduce the GIC with any periods, we constructed one-layer model with uniform conductor and calculated the electric field (IEF) induced by By using the convolution of dBy/dt and the step response of the conductor. The IEF is found to be correlated with the GIC for long periods (cc > 0.9), while the GIC-By correlation remains better for short periods. To improve the model, we constructed a two-layer model with highly conductive upper and less conductive lower layers. The IEF is shown to reproduce the GIC with cc > 0.9 for periods ranging from 1 min to 24 hours. The model is applied to the GIC measured at lower latitudes in Japan (25.3º GML) with strong By dependence. The mechanism of the strong By dependence of the GIC remains an issue, but a possible mechanism for the daytime GIC is due to the zeroth-order transverse magnetic (TM0) mode in the Earth-ionosphere waveguide, by which the ionospheric currents are transmitted from the polar to equatorial ionosphere.